Human Insecurity and Security Governance amid Conflict and Crisis in Nigeria - Paul Atagamen Aidonojie; Eregbuonye Obieshi; Ismaila Hassan; Omobolanle Omolola Ikpotokin; Collins Ekpenisi (Sekolah Tinggi Ilmu Hukum Adhyaksa, 2026)
Human insecurity continues to pose a serious challenge in Nigeria as violent conflicts and public health crises threaten lives, property, livelihoods, and social stability. Although security agencies have a fundamental responsibility to protect citizens and maintain public order, persistent criminal activities and recurring social conflicts reveal significant weaknesses in the existing security governance system. This study examines how violent conflicts and pandemic crises influence human insecurity in Nigeria and evaluates the effectiveness of security agencies in responding to these threats. The study applies a hybrid research method that combines doctrinal legal analysis with empirical research. The empirical investigation involved 414 respondents randomly selected from states across Nigeria's six geopolitical zones. The study analyzes the collected data through descriptive and analytical methods and examines the relevant legal and institutional frameworks governing public security. The findings show that violent conflicts and pandemic crises create social and economic conditions that increase vulnerability to crime and deepen human insecurity. The study also finds that limited institutional capacity, inadequate coordination, insufficient technological resources, and weak responses to underlying social, economic, political, and public health problems restrict the ability of security agencies to prevent crime effectively. The study concludes that Nigeria must strengthen security governance through an integrated approach that addresses the causes of violent conflict and public health vulnerability. Stronger institutional coordination, adequate resources, modern crime prevention technology, and responsive social policies can improve the capacity of security agencies to protect citizens and reduce human insecurity during periods of crisis.